Labor integration of immigrant population: the cases of Queretaro and Tlaxcala in the central region of Mexico - Cervantes-Castillo, Yanett; Lara-Lara, Jaime (Universidad Autónoma del Estado de México, 2018)
The objective of this research is to analyze the labor integration of recent immigrants in the labor markets of Querétaro and Tlaxcala, in a regional context of changes in the patterns of distribution of the workforce and segmentation of the labor market in the central region of Mexico. We use the formal/informal dichotomy as operational criteria to compare the probability of entering in one of the segments between migrants and natives. Migrants come mostly from Mexico City and Mexico State, have high levels of schooling, and are inserted in occupations such public servants, directors, leaders, professionals, technicians and traders, with less likelihood of being informal, even controlling for sociodemographic and occupational characteristics.